The Representation of Fujianti Utami's Identity on Instagram @Fuji_An: A Symbolic Interactionism Theory Approach: Representasi Identitas Fujianti Utami di Instagram @Fuji_An: Pendekatan Teori Interaksionisme Simbolik - Wulansari, Fitri Retno; Ifanisari, Irma Fahriza (Universitas Muhammadiyah Sidoarjo, 2025)
This research aims to analyze the representation of Fujianti Utami's identity, a social media influencer currently popular among young people, through her personal Instagram account, @fuji_an, using the symbolic interactionism theory approach. Social media, particularly Instagram, has become a strategic platform for individuals to construct and represent their identity through visual content, text, and social interactions. This study employs a qualitative method with content analysis to examine Fujianti Utami’s posts, including photos, videos, captions, and responses to followers. The symbolic interactionism theory is applied to understand how Fujianti constructs her identity through symbols, social interactions, and meanings interpreted by herself and her audience. The findings indicate that Fujianti's identity on Instagram represents a personal image that is relaxed, approachable to her audience, yet professional as a public figure. This identity is strategically managed to maintain popularity among young people. In conclusion, the @fuji_an account serves not only as a space for self-expression but also as a medium for building and reinforcing her image as a relevant and well-liked social media influencer. Highlights: Identity Construction – Fujianti Utami shapes her online persona through visuals, captions, and interactions, reflecting a balance between relatability and professionalism. Symbolic Interactionism – Her identity is built through symbols and social interactions, where meanings are co-created by both her and her audience. Strategic Image Management – The @fuji_an account functions as both a personal expression platform and a tool to maintain her relevance and popularity among young audiences. Keywords: Identity, Symbolic Interactionism, Instagram, Fujianti Utami, Influencer, Youth.